Quality Control Analysis Using the Seven Quality Control Tools in the Production Process of Crinkle Culotte Pants at CV Damar Konveksi - Yahya Zulkarnain; Maulida Butar Butar; Alsen Medikano; Renaldy Wicaksono (Asosiasi Dosen Muda Indonesia, 2026)
The garment manufacturing industry in Indonesia faces challenges in maintaining product quality, particularly in the production of crinkle culotte pants at CV Damar Konveksi. Product defects, especially in the sewing and finishing stages, have resulted in lower quality and production efficiency. Objective: This study aims to analyze and improve quality control in the production process of crinkle culotte pants at CV Damar Konveksi, identifying dominant defects and their causes to recommend corrective actions. Methodology: A quantitative approach was used, collecting primary data from direct observations and secondary data from internal records. Data were analyzed using check sheets, scatter diagrams, control charts, Pareto diagrams, and fishbone diagrams to identify defect types, frequencies, and root causes. Findings: Out of 450 units produced, 21 were defective (4.6% of total production). The Pareto diagram revealed that asymmetrical stitching and excessive sewing threads accounted for 71.4% of the defects. Control chart analysis showed the process remained within control limits, though significant quality fluctuations occurred across periods. The fishbone diagram identified human factors, suboptimal work methods, and poor machine conditions as the main causes of defects. Implications: The study recommends implementing operator training, regular machine maintenance, better enforcement of standard operating procedures, and enhancing the quality inspection system to reduce defects and improve production efficiency. Originality: This research provides valuable insights into quality control within garment manufacturing, offering a practical framework for improving product quality and operational efficiency. The use of the Seven Quality Control Tools in CV Damar Konveksi adds originality by providing actionable recommendations for similar manufacturing environments.